Grain Sorghum Cost-Return Budget in South Central Kansas - Dhuyvetter, Kevin C. (My University, 2000)
This publication projects a budget that reflects expected income and costs based on grain sorghum production in south central Kansas.
MF575_2000_10
Keywords: MF575; Economics; Crops; MF